Ensaio clínico randomizado comparando o RIA com o fresamento convencional seguido de espaçador de cimento com antibiótico, para o tratamento da infecção pós haste intramedular do fêmur e da tíbia. - Finelli, Carlos Augusto [UNIFESP] (2018)
The majority of studies on post-osteosynthesis intramedular infection (POII) are retrospective and with a limited number of cases. Reaming can be performed using the conventional reaming (CR) method or by the reamer/irrigator/aspirator (RIA) system. Until now there have been no comparative studies between these two methods. OBJETIVE: Evaluate the efficacy of the RIA system alone and CR followed by antibiotic cement spacer rod, in the treatment of POII. MATERIALS AND METHODS: A randomized clinical study was carried out between October 2013 and August 2015, with a cohort of 44 patients who had been clinically and radiologically diagnosed with chronic osteomyelitis of the femur and/or tibia. Patients were divided into two groups, RIA and conventional reaming. They were given antibiotic therapy, according to their antibiogram results, for a period of six weeks. Follow-up evaluations, both clinical and radiological, were performed after 1, 3, 6, 12, and 24 months. RESULTS: After 24 months, the rate of infection control was similar between the two groups, 87% in the RIA group and 95.5% in the conventional reaming group (p=0.6). The most common bacteria isolated in both methods of treatment was S. Aureus, in 40.4% of patients, followed by S. Epidermis in 12.3% and coagulase-negative staphylococci (CoNS) 10.6%. CONCLUSION: The study concludes that only the RIA (Reamer/Irrigator/Aspirator) system showed the same efficacy when compared with conventional reaming followed by antibiotic cement spacer.